Glycine Betaine Transport in Lactococcus lactis Is Osmotically Regulated at the Level of Expression and Translocation Activity - van der Heide, Tiemen (American Society for Microbiology (ASM), 2000)
Microorganisms react upon hyperosmotic stress by accumulating compatible solutes. Here we report that Lactococcus lactis uses a transport system for glycine betaine that, contrary to earlier observations (D. Molenaar et al., J. Bacteriol. 175:5438–5444, 1993), is osmotically regulated at the levels of both expression and transport activity.